2009
DOI: 10.1152/jn.90900.2008
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Decline in Supragranular Long-Term Synaptic Plasticity by Increased Inhibition During the Critical Period in the Rat Primary Visual Cortex

Abstract: Jang HJ, Cho KH, Kim HS, Hahn SJ, Kim MS, Rhie DJ. Age-dependent decline in supragranular long-term synaptic plasticity by increased inhibition during the critical period in the rat primary visual cortex. J Neurophysiol 101: 269 -275, 2009. First published October 29, 2008 doi:10.1152/jn.90900.2008. Supragranular longterm potentiation (LTP) and depression (LTD) are continuously induced in the pathway from layer 4 during the critical period in the rodent primary visual cortex, which limits the use of supragran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 42 publications
3
23
0
Order By: Relevance
“…These findings suggest important roles for 5-HT in the regulation of the critical period in visual cortical plasticity. In a previous study, we reported an age-dependent decline of both LTP and LTD during the critical period in the rat visual cortex and the decrease in long-term synaptic plasticity was closely related to the degree of inhibitory influence [28]. In another study, we confirmed the inhibitory effect of 5-HT on LTP induction [29].…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…These findings suggest important roles for 5-HT in the regulation of the critical period in visual cortical plasticity. In a previous study, we reported an age-dependent decline of both LTP and LTD during the critical period in the rat visual cortex and the decrease in long-term synaptic plasticity was closely related to the degree of inhibitory influence [28]. In another study, we confirmed the inhibitory effect of 5-HT on LTP induction [29].…”
Section: Introductionsupporting
confidence: 66%
“…To further elucidate the role of 5-HT, the effect of 5-HT on LTD induction was investigated by bath application of 5-HT. In a previous report, we found that short-duration, high-intensity stimulation recruited more inhibition, and that LTD could not be induced in older animals with short-duration stimulation [28]. For example, LTD could be induced by 0.1-msec and 0.2-msec stimulation in 3-week-old rats, but only 0.2-msec stimulation could induce LTD in 5-week-old rats.…”
Section: -Ht Inhibition On the Induction Of Ltdmentioning
confidence: 61%
“…In the visual cortex, inhibition is reportedly involved in the sculpting of columnar architecture [4], the processing of features of visual input [5], the regulation of the induction of long-term synaptic plasticity [6], and the regulation of the timing of critical period [7]. Since inhibition matures during postnatal development of the visual cortex [8,9], the effect of inhibition on these processes changes during development, and thus inhibitory maturation exerts its effect on the functional development of the visual cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Since inhibition matures during postnatal development of the visual cortex [8,9], the effect of inhibition on these processes changes during development, and thus inhibitory maturation exerts its effect on the functional development of the visual cortex. For example, whereas inhibitory influence over a certain threshold level is necessary for the induction of long-term synaptic plasticity at the early postnatal developmental stage [10], further development of inhibition suppresses the induction of plasticity [6,11]. Furthermore, the kinetic features of inhibition are known to change during development of the visual cortex [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation